Inovasi Pemerintah Desa dalam Mewujudkan Ketahanan Pangan di Desa Lumbungsari Kecamatan Lumbung Kabupaten Ciamis - Wahyu Rahmat Hidayah; Erlan Suwarlan; Kiki Endah (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This research is motivated by the suboptimal Innovation of Village Government in Realizing Food Security in Lumbungsari Village, Lumbung District, Ciamis Regency. The purpose of this study is to determine the Innovation of Village Government in Realizing Food Security in Lumbungsari Village, Lumbung District, Ciamis Regency. The method used in this study is a qualitative descriptive research method. Data collection techniques include: Observation, Interviews and documentation. Data processing techniques in this study are: data reduction, data presentation, and drawing conclusions. The results of the study show that the Innovation of Village Government in Realizing Food Security has not been running optimally. From the results of the observation, several indicators of problems were found related to the Innovation of Village Government in Realizing Food Security in Lumbungsari Village, Lumbung District, Ciamis Regency, including lack of funds to support food security, lack of adequate facilities and infrastructure to support agricultural activities, low public awareness to achieve new innovations, and low community skills in using information technology and applications.